Association of Stearoyl-CoA Desaturase Gene Polymorphisms on Milk Fatty Acid Composition of Holstein Friesian Cows in Indonesia - Azis, R.; Anggraeni, A. (Tropical Animal Science Journal, 2023)
Milk fatty acid composition determines milk quality and the health of consumers. Stearoyl-CoA desaturase (SCD) gene controls lipid metabolism in the mammary gland, which plays an essential role in catalyzing saturated fatty acids (SFA) into monounsaturated fatty acids (MUFA). This study aimed to analyze the genetic diversity of the SCD gene and its effect on the milk fatty acid quality of Holstein Friesian (HF). Genetic variants were identified on 226 HF cattle from various dairy breeding Stations in West Java, Central Java, and East Java in Indonesia. Blood samples were extracted and amplified using Real-Time Polymerase Chain Reaction (RT-PCR) technique based on TaqMan Probe to determine the genotype of the SCD gene at g.10153A>G locus. Milk samples were analyzed by Gas Chromatography and Mass Spectrometry (GCMS) on 48 lactating cows. The SCD g.10153A>G produced three genotypes, namely AA (0.112), AG (0.640), and GG (0.271); and two alleles, namely A (0.409) and G (0.591). Genotype polymorphism of the SCD g.10153A>G had a significant effect (pG SNP (AG genotype) could be one of the candidates as a genetic marker to assist selection in reducing SFA and increasing MUFA in the milk content of HF cows in Indonesia.